The Comparison of Short-Term Postoperative Pain in Single- versus Multiple-Visit Root Canal Treatment: A Systematic Review and Meta-Analysis Study - Armin Izadpanah; Ailar Javaheripour; Azam Maleki; Mahdieh Alipour; Hossein Hosseinifard; Simin Sharifi; Solmaz Maleki Dizaj (Pain Research and Management)
Postoperative pain after root canal therapy (RoCT) is an unpleasant experience for patients, and it could be affected by different factors. The times of visits could be one of these factors that were evaluated in various studies. However, there is inconsistent evidence on the relation between postoperative pain and the times of visits. Therefore, the current systematic review aimed to summarize the results of these studies and meta-analyze them. For this purpose, a comprehensive search was conducted in four main databases (Cochrane Database of Systematic Reviews, Web of Science, PubMed, and Scopus databases) for related English articles from 1978 to August 2020. The quality of studies was evaluated using the Delphi checklist. The heterogeneity of studies was determined by I2 statistic, and publication bias was assessed using the funnel plot and the Begg test. The results were presented by using relative ratio (RR) estimates and standard mean difference (SMD) with its 95% confidence intervals (CI) using a random-effects model. Initial searches from mentioned databases identified 1480 papers; of which only 27 of them met the inclusion criteria. In quality assessment, thirteen studies had quality scores of more than 7, two studies had 4 scores, and the rest had 5 scores. Overall, based on the available evidence, the meta-analysis showed that the risk of postoperative pain in single-visit was 1.02 times (CI 95% (0.99, 1.19), I2 = 60.7%, p=0.001) higher than that of the multiple-visit treatment. The mean difference of postoperative pain in single-visit was −0.30 (CI 95% (−0.36, −0.25), I2 = 0.94.4, p=0.001) compared with the multiple-visit treatment. Based on the results of this meta-analysis, the risk of postoperative pain in single-visit RoCT was higher than that in multiple-visit RoCT with acceptable statistical heterogeneity and moderate quality of the studies.